Spin-lattice relaxation in the triplet state of the buried tryptophan residue of ribonuclease T1. - Ghosh, S (1986)
The individual spin-lattice relaxation (SLR) rate constants (Wij) between the lowest triplet sublevels of the lone tryptophan residue buried in the interior of the globular protein ribonuclease T1 have been reported in the temperature range 1.2 to 3.0 K in zero applied magnetic field. The SLR rate constants between spin sublevels exhibit marked anisotropy in their magnitudes and also show appreciable sensitivity to the glycerol content of the aqueous cryogenic matrix. The temperature dependence of SLR suggests that in the temperature range investigated a direct process contributes dominantly to the SLR in this protein.